2020
DOI: 10.11609/jott.5815.12.14.16927-16943
|View full text |Cite
|
Sign up to set email alerts
|

Elevational pattern and seasonality of avian diversity in Kaligandaki River Basin, central Himalaya

Abstract: This study explored bird diversity, seasonal variation, and associated factors along an elevational gradient in an important biodiversity area (IBA) of central Nepal: the Kaligandaki River basin of Annapurna Conservation Area.  The field survey was carried out in 2019 over two seasons, winter (January and February) and summer (May and June) using the point count method.  A total of 90 sampling plots were set up from elevations of 800m (Beni) to 3,800m (Muktinath).  Data for variables including the number of fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 68 publications
(87 reference statements)
2
5
0
Order By: Relevance
“…However, the number of bird species recorded in this study seemed low compared to the record of 318 species found in SNNP (BirdLife Nepal, 2018) which is the official checklist of birds that covers all sites of SNNP in all four seasons over a long period of time but our study was only limited in one trekking trail i.e., Sundarijal and only covers monsoon season. Insectivores were the most abundant species feeding guild in SNNP which is supported by many other studies on birds (Katuwal et al, 2016;Neupane, Khanal, Gyawali and Chalise, 2020;Pandey, Khanal, and Chalise, 2020). Bird Species belonging to Order Passeriformes were numerically most abundant in SNNP which is similar to study done by (Husein and Sultan, 2009) A similar pattern was also observed in other studies (McCain, 2009;Neupane et al, 2020;Rahbek, 1995;Santhakumar, Arun, Sony, Murugesan and Ramesh, 2018).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, the number of bird species recorded in this study seemed low compared to the record of 318 species found in SNNP (BirdLife Nepal, 2018) which is the official checklist of birds that covers all sites of SNNP in all four seasons over a long period of time but our study was only limited in one trekking trail i.e., Sundarijal and only covers monsoon season. Insectivores were the most abundant species feeding guild in SNNP which is supported by many other studies on birds (Katuwal et al, 2016;Neupane, Khanal, Gyawali and Chalise, 2020;Pandey, Khanal, and Chalise, 2020). Bird Species belonging to Order Passeriformes were numerically most abundant in SNNP which is similar to study done by (Husein and Sultan, 2009) A similar pattern was also observed in other studies (McCain, 2009;Neupane et al, 2020;Rahbek, 1995;Santhakumar, Arun, Sony, Murugesan and Ramesh, 2018).…”
Section: Discussionsupporting
confidence: 87%
“…Insectivores were the most abundant species feeding guild in SNNP which is supported by many other studies on birds (Katuwal et al, 2016;Neupane, Khanal, Gyawali and Chalise, 2020;Pandey, Khanal, and Chalise, 2020). Bird Species belonging to Order Passeriformes were numerically most abundant in SNNP which is similar to study done by (Husein and Sultan, 2009) A similar pattern was also observed in other studies (McCain, 2009;Neupane et al, 2020;Rahbek, 1995;Santhakumar, Arun, Sony, Murugesan and Ramesh, 2018). This is due to significant decrease in plant species richness with increase in elevation along sub-tropical gradient in the Himalayas which had provided different habitats for various avian species (Bhattarai, Vetaas and Grytnes, 2004).…”
Section: Discussionsupporting
confidence: 87%
“…Most studies in the Himalayan region show a hump-shaped pattern of bird richness, with the greatest diversity found at intermediate elevations [ 23 , 24 , 25 ]. However, a few studies in Nepal have also reported a monotonic decline of bird richness with increasing elevation [ 26 , 27 ]. As no studies have covered the entire elevational range of the Himalayas in Nepal, we recommend further studies that address the entire elevational gradients in the Nepalese Himalayas to generalize patterns of bird response towards elevation and other factors affecting their distribution.…”
Section: Discussionmentioning
confidence: 99%
“…However, the impact of management intervention on bird diversity and different feeding guilds (i.e., species exploiting resources in a similar manner) varies with topography (e.g., mountains versus plains), climate (e.g., tropical versus temperate areas), and seasonal changes [ 22 , 23 ]. Elevation gradient is another important factor in shaping bird assemblages in the Himalayas; most studies report hump-shaped patterns with the highest diversity at intermediate elevations [ 23 , 24 , 25 ], while some have found a monotonic decline with increasing elevation [ 26 , 27 ]. Few studies have examined the impact of forest management practice on bird community composition in South Asia, including Nepal (see [ 12 ]).…”
Section: Introductionmentioning
confidence: 99%
“…It is pressurized by population surge and anthropogenic development increasing the intensity of urbanization. Most importantly, Butwal City lies along the northsouth migration route of trans-Himalayan birds along the Kaligandaki River Valley (Prins and Namgail, 2017;Neupane et al, 2020). Hence, it is important to know the bird species composition and effects of that rampant urbanization poses to the bird in Butwal City.…”
Section: Introductionmentioning
confidence: 99%